Análise comparativa da infiltração marginal apical de três cimentos endodônticos através de um processo de diafanização - Villela, Alexandre Mascarenhas (2007)
The success of any endodontic treatment is directly related to the correct execution of all its phases, ranging from diagnosis through its proservation. The obturation of the root canal system does not escape this rule and deserves special attention, since that is the phase which finishes the treatment. The filling material must seal the whole root canals system, a space previously filled by the root pulp, promoting a three-dimensional air-tight sealing. Throughout the years, various materials have already been tested, however the use of gutta-percha (solid material) associated with an endodontic sealer (plastic material) is nowadays largely accepted as a best practice among top level professionals. Gutta-percha must be the main material of the obturation, occupying the largest possible space of the light of the root canal system. However, the endodontic sealer has shown direct influence in the success of the endodontic treatment. A countless number of researches have been and are still being carried out as an attempt to develop a sealer which includes all the physical-chemical and biological characteristics of a filling material. The present study had as objective a comparative evaluation of the apical marginal sealing capability of the sealers: Sealer 26®, Acroseal® and EndoREZ®. All the experiments were carried out at the Endodontic Research Laboratory of the College of Odonthology of the University of the State of Rio de Janeiro. The conclusion was that none of the sealer tested was capable of avoiding apical marginal leakage in all teeth tested. According to statistical analyses, Sealer 26® and Acroseal® sealers did not present statistically significant differences, while EndoREZ® sealer presented a much inferior and statistically significant result.